The Studi Kasus: Multidrug Resistance Terhadap Bakteri Escherichia coli pada Ayam Broiler di Pasar Tradisonal Balongsari, Surabaya - PUTRI, MARIANA FEBRILIANTI (Fakultas Kedokteran Hewan Universitas Wijaya Kusuma Surabaya, 2024)
Escherichia coli is one of the causes of colibacillosis in poultry. Escherichia coli resistant can be transmitted to humans through animal products and animal waste in the environment as a problem in humans and animals. Antibiotics can be continues to experience resistance which will lead to multidrug-resistant (MDR). The aim of this research was to detect multidrug resistance against Escherichia coli bacteria in broiler chickens at the Balongsari traditional market, Surabaya. The samples used were 24 cloacal swabs from broiler chickens. Isolated and identified samples were culture media, in the form of eosin methylene blue agar (EMBA), Gram staining, Triple Sugar Iron Agar (TSIA), Sulfide Indole Motility (SIM), Simmons Citrate Agar (SCA), indole test, methyl Voges Proskauer (MR-VP). Detection of multidrug resistance confirmation with Mueller-Hinton Agar (MHA) media. The results of isolation and identification of Escherichia coli bacteria in this study showed 83%. Antibiotic resistance testing using the diffusion method showed that the highest antibiotic resistance results occurred in the antibiotics ciprofloxacin 85%, tetracycline 60%, kanamycin 45%, chloramphenicol 25% and aztreonam 20%. The multidrug resistance results showed that Escherichia coli bacteria was 45%. This data confirms the existence of Multidrug resistance against Escherichia coli bacteria in broiler chickens at the Balong Sari traditional market in Surabaya which has an impact on public health.